Complete reversal of the clinical symptoms and image morphology of ketamine cystitis after intravesical hyaluronic acid instillation: A case report. Issue 28 (July 2018) - Ou, Ying-Lun; Liu, Chin-Yu; Cha, Tai-Lung; Wu, Sheng-Tang; Tsao, Chih-Wei
Abstract: Rationale: Ketamine abuse is an emerging issue in many countries, and ketamine cystitis (KC) is a growing disease which more and more urologists may encounter with. There was no gold standard diagnostic criteria of ketamine cystits established yet, but well-accepted with the positive substance abuse history and clinical symptoms. The clinical presentation of ketamine cystitis varies and may mimic those presented in interstitial cystitis (IC), such as voiding frequency, urgency with urge incontinence, dysuria, nocturia, burning sensation during urination, post urination pain, painful hematuria, and small bladder capacity, but there are still differences that KC presented with more urgency, hematuria, pyuria and upper urinary tract involvement such as ureteral stenosis, vesico-ureteric reflux, hydronephrosis and renal function impairment. Patient concerns: We presented an interesting case with a 36-year-old man who's symptoms mimic acute prostatitis but there was no positive pathogen been cultured. The computed tomography (CT) findings revealed asymmetrical bladder wall thickening, which misleading us to the impression of bladder cancer. After the cystoscopy with bladder biopsy, the pathology revealed severe inflammation without malignancy. After that, we prescribed anticholinergic agent, beta-3 agonist and nonsteroidal anti-inflammatory drug (NSAID) for him, but in vain. Diagnoses: Erosive cystitis with prominent infiltration by eosinophils, lymphocytes, neutrophils and plasma cells. Interventions: Then we introduced hyaluronic acid (HA) instillation, once a week for total 10 times. Outcomes: After the treatment, his urgency, frequency, nocturia improved and his bladder capacity increased from less than 100ml to 350mL per urination. The following magnetic resonance imaging (MRI) and bladder biopsy result revealed complete reversal. Lessons: To our literature review, this is the first case of ketamine cystitis presented with asymmetrical bladder wall thickening, which may be considered as an irreversible change, but turns out complete reversal of the clinical symptoms and image morphology after merely intravesical hyaluronic acid instillation